The rise of the West : - McNeill, William Hardy (The University of Chicago Press, 1963)
Contents: The era of middle Eastern dominace to 500 B. C.; Eurasian cultural balance 500 B. C. - 1500 A. D.; The era of Weatern dominance, 1500 A.D. to the present.